2008
DOI: 10.1507/endocrj.k07-086
|View full text |Cite
|
Sign up to set email alerts
|

Significant Association of Serum Albumin with Severity of Retinopathy and Neuropathy, in Addition to That of Nephropathy, in Japanese Type 2 Diabetic Patients

Abstract: Abstract. Objective: The aim of this study was to determine the association between serum albumin and the severity of microvascular complications and presence of coronary artery disease in type 2 diabetic patients. Patients and Methods: The presence of diabetic complications was assessed in a total of 130 Japanese patients with type 2 diabetes mellitus. Retinopathy was classified as absent, simple or proliferative diabetic retinopathy. Neuropathy was considered to be present when the patient showed absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 9 publications
4
26
0
Order By: Relevance
“…Therefore, microvascular complications such as diabetic nephropathy and diabetic neuropathy go hand in hand in persons with diabetes. [15] The limitation of the present study is the use of a single measurement (biothesiometry) for diagnosing neuropathy; however, other diagnostic measures such as nerve conduction studies and neuropathy symptom score estimations are somewhat cumbersome in large epidemiological studies. Another limitation is the point estimation of risk factors which cannot prove a causal association.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, microvascular complications such as diabetic nephropathy and diabetic neuropathy go hand in hand in persons with diabetes. [15] The limitation of the present study is the use of a single measurement (biothesiometry) for diagnosing neuropathy; however, other diagnostic measures such as nerve conduction studies and neuropathy symptom score estimations are somewhat cumbersome in large epidemiological studies. Another limitation is the point estimation of risk factors which cannot prove a causal association.…”
Section: Discussionmentioning
confidence: 95%
“…found that there was no significant association of patient age, duration of dialysis, etiology of uremia, or efficiency of dialysis with the occurrence of neuropathy. A significant association of serum albumin with neuropathy severity has been reported in patients with diabetes . Chronic inflammation in patients with CKD might lead to a decrease in albumin synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…A significant association of serum albumin with neuropathy severity has been reported in patients with diabetes. 35 Chronic inflammation in patients with CKD might lead to a decrease in albumin synthesis. Low serum albumin seen in our patients might have been due to albuminuria or decreased albumin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a cohort study of 343 T2DM patients demonstrated that hypoalbuminemia was independently associated with progression of nephropathy as evaluated by rate of decline of estimated glomerular filtration rate [41]. Additionally, in a Japanese study comprising 130 T2DM patients [42], Iwasaki et al reported that serum albumin was significantly associated with the severity of neuropathy, retinopathy, and nephropathy. With respect to neuropathy, it is notable that serum albumin was independently related to median motor nerve CV after adjusting for three variables (age, sex, serum C-reactive protein).…”
Section: Discussionmentioning
confidence: 99%